ANALISIS TERHADAP OPTIMALISASI VOLUME PENJUALAN MELALUI PENYERAHAN PEKERJAAN KEPADA KARYAWAN OUTSOURCING PADA PT WARNA AGUNG DI BANDAR LAMPUNG - Erlina Erlina; DODDY Doddy (Universitas Bandar Lampung (UBL), 2021)
Outsourcing in Indonesian labor law is defined as the contracting of workers and providers of labor services. The legal arrangements for outsourcing in Indonesiaare regulated in Articles 64, 65 and 66 of Law Number 13 of 2003 concerningManpower and Decree of the Minister of Manpower and Transmigration of theRepublic of Indonesia No. Kep.101/Men/VI/2004 of 2004 concerning Procedures forLicensing of Companies Providing Workers/Labourers.The results of the research are the process of handing over work to outsourcingemployees at PT Warna Agung, namely PT Warna Agung contacting PT Bina CiptaAbadi as an outsourcing company, then formulating a Work Agreement for charteringwork to support the company's operations. Optimization of sales volume throughhanding over of work to outsourced employees is an effort by PT Warna Agung toobtain competent and experienced workers, especially in the marketing field. Efforts toprotect the legal rights of outsourced employees at PT Warna Agung in BandarLampung are to create legal certainty regarding the rights of outsourced employees soas to ensure the fulfillment of the rights of outsourced employees.The advice given is that PT Warna Agung should pay more attention tooutsourcing employees in fulfilling employee welfare in the future. Then workers shouldunderstand and understand the rights and obligations agreed in the outsourcing workagreement and the government should carry out stricter supervision so that there are no legal violations of the rights of outsourced employees.